Public finance - Eckstein, Otto. (Englewood Cliffs, N.J. : Prentice-Hall, 1973)
This book is an introduction to public finance, the study of the revenue and expenditure activities of government. It discusses budgets, taxes, government expenditures, and public debts.
Includes bibliographical references: p. 124-125.
osc 10/01/2019
Loans
Keywords: Finance, Public